2014
DOI: 10.1016/j.socscimed.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Conditional health-related benefits of higher education: An assessment of compensatory versus accumulative mechanisms

Abstract: A college degree is associated with a range of health-related benefits, but the effects of higher education are known to vary across different population subgroups. Competing theories have been proposed for whether people from more or less advantaged backgrounds or circumstances will gain greater health-related benefits from a college degree. This study draws on data from the National Longitudinal Study of Adolescent Health (Add Health) and recently developed models for analyzing heterogeneous treatment effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 54 publications
3
69
0
Order By: Relevance
“…9 Net college returns for health or well-being, within or across age or cohort, reflect diverse countervailing social mechanisms or processes, making simple explanations of them likely incomplete (see Bauldry 2014Bauldry , 2015Conti and Heckman 2010;Schafer et al 2013). These social forces include, but are not limited to, shifts in the gendering of educational expectations and attainments; educational content, quality, or expansion across cohorts; economic conditions influencing labor market entry, placement, and persistence; rates of marriage and changing patterns in educational homogamy; domestic division of labor and separate spheres; and shifting social mobility and intergenerational correlations in educational attainment (Cutler and Lleras-Muney 2010;DiPrete and Buchmann 2006;Lawrence 2017;Mirowsky and Ross 2003;Ross and Mirowsky 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Net college returns for health or well-being, within or across age or cohort, reflect diverse countervailing social mechanisms or processes, making simple explanations of them likely incomplete (see Bauldry 2014Bauldry , 2015Conti and Heckman 2010;Schafer et al 2013). These social forces include, but are not limited to, shifts in the gendering of educational expectations and attainments; educational content, quality, or expansion across cohorts; economic conditions influencing labor market entry, placement, and persistence; rates of marriage and changing patterns in educational homogamy; domestic division of labor and separate spheres; and shifting social mobility and intergenerational correlations in educational attainment (Cutler and Lleras-Muney 2010;DiPrete and Buchmann 2006;Lawrence 2017;Mirowsky and Ross 2003;Ross and Mirowsky 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Following other research in this area (Bauldry 2014(Bauldry , 2015Conti and Heckman 2010;Lawrence 2017;Schafer et al 2013), I designated the upper two categories as having received a fouryear or bachelor's degree (1 = college or higher, 0 = less than four-year college). 2 …”
Section: Educational Attainment: College (Bachelor's) Degreementioning
confidence: 99%
See 1 more Smart Citation
“…In another study of the effects of education on depression with socioeconomic resources in childhood as the measure of advantage/disadvantage using data from the multiple waves of the Survey of Health, Ageing, and Retirement in Europe, Schaan (2014) also found that people from poor families benefited more from education than people from better-off families, a pattern that remained consistent over the later life course (ages 50 and up). Additional evidence in support of the resource substitution hypothesis comes from analyses examining the effects of education on physical health (Ross and Mirowsky 2011; Schafer et al 2013); however, Bauldry (2014) found support for resource multiplication in an analysis of self-rated health among young adults.…”
Section: Who Benefits More From Educationmentioning
confidence: 99%
“…In contrast to the Schafer et al (2013) and Bauldry (2014) studies that draw on similar models for heterogeneous treatment effects, the present study focuses on mental rather than physical health, in particular, depressive symptomology. In addition, the present study examines heterogeneity in the effect of both completing some college education and attaining a four-year college degree.…”
Section: Who Benefits More From Educationmentioning
confidence: 99%